The Counsellor as a Cause and Cure of Client Resistance - Mahrer, Alvin R.; Murphy, Lynn; Gagnon, Robin; Gingras, Normand (Canadian Journal of Counselling and Psychotherapy, 2007)
Three ways are proposed in which the counsellor may be seen as a major contributor to client resistance: (a) the counsellor wants the client to be and to behave in counsellor-imposed ways; (b) the counsellor actively constructs a complementary role that the client is to fulfill; and (c) the counsellor maintains an entrenched belief in the truth of "client resistance." Counsellor strategies are suggested to reduce each of these determinants and thereby move in the direction of significant reduction of counsellor-induced client resistance.